PENGEMBANGAN SUMBER DAYA MANUSIA MENUJU SEKOLAH ISLAM UNGGULAN (STUDI KASUS di SEKOLAH MENENGAH PERTAMA ISLAM SUNAN GIRI WAGIR MALANG) - Moh Imron; Mochamad Nurcholiq (STAI Ma'had Aly Al-Hikam Malang, 2019)
The quality of education of a nation is largely determined by the quality of human resources both educators and educational staff. Therefore, it is a necessity for every educational institution to improve the quality of teaching staff. Efforts to increase or develop it lead to one meeting point that is so that the school towards the ideals expected by all existing stakeholders. This study uses a qualitative approach to the type of case study, which research is carried out at Sunan Giri Islamic Middle School. Data collection is done using techniques: interviews, observation, and documentation. While the data obtained were analyzed through several stages namely: Condensation, data display, and verification of conclusions as well as checking the validity of the data. The process of developing human resources both educators and education personnel has been going well, but there are still shortages here and there both in terms of implementation and evaluation of the results of the development.